Analysis of transport from cylindrical surfaces subject to catalytic reactions and non-uniform impinging flows in porous media: A non-equilibrium thermodynamics approach - Alizadeh, Rasool; Karimi, Nader; Mehdizadeh, Amirfarhang; Nourbakhsh, Amireh (Journal of thermal analysis and calorimetry, 2019)
This paper investigates forced convection of heat and mass from the catalytic surface of a cylinder featuring non-uniform transpiration and impinging flows in porous media. The non-equilibrium thermodynamics including Soret and Dufour effects and local thermal non-equilibrium are considered. Through employing appropriate change of variables, the governing equations in cylindrical coordinate are reduced to nonlinear ordinary differential equations and solved using a finite difference scheme. This results in the calculation of the temperature and concentration fields as well as the local and surface-averaged Nusselt and Sherwood numbers. The conducted analyses further include evaluation of the rate of entropy generation within the porous medium. It is shown that internal heat exchanges inside the porous medium, represented by Biot number, dominate the temperature fields and Nusselt number. This indicates that consideration of local thermal non-equilibrium is of highly important. It is also demonstrated that Dufour and Soret effects can significantly influence the development of thermal and concentration boundary layers and hence modify the values of Nusselt and Sherwood numbers. In particular, it is shown that small variations in Soret and Dufour numbers can lead to noticeable changes in the average Nusselt and Sherwood numbers. Such modifications are strongly dependent upon the type of transpiration and characteristics of the impinging flow. The present work is the first analysis of non-equilibrium effects upon transport by stagnation flows around the curved surfaces embedded in porous media.